+0  
 
0
3
1
avatar+794 

Evaluate a^3 - \dfrac{1}{a^3} if a^2 - a - 1 = 0.

 Jan 5, 2024
 #1
avatar+126665 
+1

\(a^3 - \dfrac{1}{a^3} if a^2 - a - 1 = 0 \)

 

 

a^2 - a    = 1

 

a^2 -a + 1/4   = 1 +1/4

 

(a - 1/2)^2  =  5/4

 

a -1/2  = sqrt (5) / 2                                a - 1/2  =  -sqrt (5)/2

 

a = Phi = [1 + sqrt 5 ]  / 2                               a =  -phi  =   [1 -sqrt 5 ]  / 2

 

Phi = 1/phi     

 

a^3  - 1/a^3

 

[Phi]^3 -  [1/Phi]^3 =                          ( -phi )^3  - (1/-phi)^3  =

 

Phi^3 - phi^3                                      -phi^3  +   1/phi^3 

 

                                                               -phi^3 + Phi^3

 

                                                                Phi^3  - phi^3

 

 

Phi^3  - phi^3   =

 

(Phi - phi)(Phi^2 + 1 + phi^2)             {Phi- phi  = 1 }              

 

    (1) (Phi^2  + 1  +  (phi^2 )  

 

Phi^2 + phi^2  =   [ [sqrt (5) +1 ] / 2 ] ^2   +   [ [sqrt 5 -1] /2]^2  =  

 

[5+2sqrt5 + 1 ] / 4   +  [ 5  - 2sqrt 5) + 1 ] / 4   =

 

(6/4) + (6/4)  =

 

12/4  = 3

 

So

 

Phi^3  - 1/(Phi)^3 = 

 

Phi^3 - phi^3

 

(Phi - phi)  (  1 + Phi^2 + phi^2 )  =

 

(1)  (1 + 3)  =

 

(1) (4)  =  

 

   

 

 

 

cool cool cool                  

 Jan 5, 2024
edited by CPhill  Jan 5, 2024

1 Online Users